Endovascular laser ablation management of pediatric Klippel trenaunay syndrome: a case report - Annisa; Ivan Joalsen MT; Michael Caesario (Indonesian Vascular Access Association (IVAA), 2023)
Introduction: Klippel trenaunay syndrome (KTS) is a rare and complex congenital vascular anomaly as a combination of vascular capillary malformations (port wine stain), venous malformations (VM) and excessive extremity growth with or without lymphatic malformations. The incident KTS is estimated to be 2 to 5 per 100,000 and found in the male gender without distinguishing race. This syndrome is rare, with a low incidence. Klippel trenaunay syndrome uses conservative management with the use of compression stockings. Other KTS management, such as minimally invasive intervention with endovascular laser ablation (EVLA) therapy, is rarely used due to the rare number of diseases. Thus, this study aims to perform the management of KTS in pediatrics. Case description: We report 11-year-old girls complaining of pain and swelling on the right leg when standing long and doing activities. Physical examination appears to show a purplish-red birthmark that arises on the surface of the skin. Ultrasound and CT scan angiography with contrast in the lower region extremities showed hypertrophy accompanied by peripheral branches in the cutaneous layer. Patients are performed endovascular laser ablation using general anesthesia. After endovascular laser ablation, the patient was treated for 2 days without any complaints. Conclusion: KTS is a rare, complex and varied syndrome that has not been found yet. KTS only performs symptomatic treatment depending on clinical and severity. Endovascular laser ablation is a minimally invasive intervention management that must be considered and has a fairly low risk and complication, especially in pediatrics.